A condition that yields potentially K14,s-graphic sequences - Yin, Meng-Xiao; Gao, Nan; Zhong, Cheng; Yang, Feng (Utilitas Mathematica, 2018)
A graphic sequence π = (d1,d,2,...,dn) is said to be potentially K14,s-graphic if there is a realization of π containing K14,s as a subgraph, where K14,s is the l×l×l×l×s complete 5-partite graph. This paper poses a condition that yields potentially K14,s,-graphic sequences for s ≥ 1 and n ≥ 13s - 4, it generalizes the result of Yin[1]. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.